Tingkat Penerimaan Masyarakat Terhadap Ikan Nila (Oreochromis niloticus) Segar Dengan Habitat Yang Berbeda - Tri Adi Wibowo; Desy Sasri Untari; Rohmatul Anwar (Samakia : Jurnal Ilmu Perikanan, 2021)
Freshwater fish has an important role in fulfilling an affordable source of animal protein, especially for areas that have limited access to fish from sea catches. Tilapia fish (Oreochromis niloticus) is one type of freshwater fish that is popular and generally consumed by many people. This study was conducted to determine the effect of community interest in the Kotabumi area, North Lampung Regency on tilapia fish that are maintained in different habitats, namely naturally grown in Lake Ranau, West Lampung Regency, and artificially in the enlargement pond owned by the community in Kotabumi area. Based on the results of the available data, it is concluded that fish habitat has an effect on people's consumption interest. Tilapia fish originating from Lake Ranau are more attractive to the community when compared to local tilapia fish that are kept in community ponds in the Kotabumi area. The organoleptic test value of fresh tilapia originating from Lake Ranau has a higher value of 7,84 ≤ µ ≤ 8,28, compared to tilapia fish from community ponds with a value of 7,52 ≤ µ ≤ 7,55